U.S. parent perspectives on media guidance from pediatric autism professionals. Issue 2 (3rd April 2021) - Alper, Meryl
ABSTRACT: Screen media guidelines for children set by medical organizations (e.g., the American Academy of Pediatrics) play a significant role in public discourse regarding media and parenting. Physician mediation theory, an adaptation of parental mediation theory, suggests that physician-patient discussion about media content (e.g., online searches) directly shapes patient engagement with said content. Little attention has been paid though as to how guidance about children's media use is delivered to parents by pediatric clinical professionals and its utility from the perspective of diverse families. Interviews and home observations were conducted with families of 26 children ages 3–13 on the autism spectrum. Two main social contexts for media guidance were identified: advising on children's media use 1) as part of therapy and 2) as recreation . Prior research indicates that physician mediation takes three forms: positive (encouraging media use), negative (discouraging), and redirective (suggesting alternatives). Within the two contexts, positive physician mediation was more prominent in therapeutic than recreational contexts. Poor and working-class families also tended to report media guidance less than upper- and middle-class families, partly due to barriers in accessing clinical care. Implications are discussed for improving physician mediation theory as well as enhancing caregiver-clinician communication about children's media use.